PEMAHAMAN KONSEPTUAL DAN KELANCARAN PROSEDURAL SISWA DALAM MATERI BENTUK AKAR DI KELAS X SMA - Nola Anggita; Yulis Jamiah; Dian Ahmad BS (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstract This research was conducted to find out conceptual understanding and procedural fluency of students on root form material in SMA Muhammadiyah 2 Pontianak. This research used descriptive method with quantitative approach. Subjects in this research were students of class X MIA with a total of 27 students. Written tests are used to collect data. Based on the analysis of research data obtained conceptual understanding of each indicator are: (1) indicator 1 is in very low category (4%); (2) indicator 2 is in very low category (34%); (3) indicator 3 included in high category (80%); (4) indicator 4 is in very low category (28%) and (5) indicator 5 is in low category (55%). The procedural fluency of students in every aspect are: (1) flexible aspects are in very low category (28%); (2) efficient aspects are in very low category (28%) and (3) accurate aspects are in very low category (37%). Conceptual understanding and procedural fluency of students are in very low category with a percentage of 40% and 31% respectively. Keywords: Conceptual Understanding, Procedural Fluency